Common Lexical Items in Lithuanian, Hindi and Sanskrit - Markevičienė, Žaneta (Kalbotyra, 2002)
It is not only linguists who know numerous common lexical items in Lithuanian and Sanskrit. But in a coherent text, one should make considerable effort to find some. It is a paradox, but Hindi texts and the spoken language are an easier source while searching for words common to Hindi and Lithuanian. There are a number of different reasons for this. First, Hindi has unbelievably numerous loan words from Sanskrit, therefore, numerous common items among Sanskrit, Lithuanian and Hindi exist presently, e. g., Lith. smakras – Hind., Skr. śmaśru ‘chin’; Lith. medus – Hind. madhu – Skr. mádhu ‘honey’, etc.Another portion of the common lexicon embraces native Hindi words (the so-called tadbhava layer). It includes common items absent in Sanskrit, e. g., Lith. kulšis – Hind. kūlhā ‘hip’; Lith. kupra – Hind. kūbar ‘hump’; Lith. bėgti ‘to run’ – Hind. bhāgnā ‘to run away’; Lith. kukurbezdalis, kukurdvelkis ‘puffball’ – Hind. kukurmuttā ‘mushroom’, etc. Some of the Hindi words are more phonetically similar to Lithuanian words than to their Sanskrit counterparts: Lith. tu – Hind. tū – Skr. tvám ‘you’; Lith. naujas – Hind. nayā – Skr. navas ‘new’; Lith. augti ‘to grow’ – Hind. ugnā – Skr. úkṣati ‘(he) grows up’; Lith. ūdra – Hind. ūd – Skr. udrás ‘otter’, etc.There are other reasons, as well. Sanskrit has only the written form, while Hindi has both the written and spoken varieties. Contemporary Hindi is closer to everyday style, and this style is the most stable in the Indo-European languages. Sanskrit used to be an elite and purified language: therefore, the most common everyday words could have been avoided in it.The article also includes a comparison of Lithuanian, Hindi and Sanskrit words according to semantic peculiarities. It also makes a couple of observations about the phonetic equivalents in all the three languages.